Analysis of the natural orbits around Io - Caritá, G. A. [UNESP]; Aljbaae, S.; Prado, A. F.B.A.; Signor, A. C. [UNESP]; Morais, M. H.M. [UNESP]; Sanchez, D. M. (Springer Nature, 2023)
The natural satellite of Jupiter, Io, is one of the most interesting bodies in the solar system and deserves to be studied in detail. Up to now, no man-made vehicle has orbited Io because the level of radiation is too high for an orbiter to stay nearby for longer periods of time. In that sense, only flyby missions have studied this body. With the advance of technology, an important step in Solar System research is to develop shields that are strong enough to make orbiter missions around Io possible in the near future. With that in mind, the present paper has the goal, as first step, of mapping possible stable orbits around Io that can accommodate a spacecraft and that do not require station-keeping maneuvers to survive. The dynamical system considers the gravity fields of the Sun, Jupiter, Saturn, Europa, Ganymede, Callisto and the non-spherical shape of Jupiter and Io. To help in this search and to better explain the reasons of stability, integral indices are used to map the less perturbed orbits to guide the numerical searches for stable orbits. We observe several regions of bounded orbits around Io. In these orbits, a relation between the perturbation indices and the duration of stability is found, demonstrating the importance of this tool in mission analyses. Several regions of bounded orbits are found in this system.
Keywords: Celestial mechanics; Numerical methods; Planets and satellites; Space vehicle